Involvement of Phosphatase and Tensin Homolog in Cyclin-Dependent Kinase 4/6 Inhibitor-Induced Blockade of Glioblastoma - Liu, Songlin; Yuan, Dun; Li, Yifeng; Qi, Qi; Guo, Bingzhong; Yang, Shun; Zhou, Jilin; Xu, Lu; Chen, Tiange; Yang, Chenxing; Liu, Junyu; Li, Buyan; et al. (Frontiers in Pharmacology, 2019)
Dysregulation of retinoblastoma (Rb) signaling pathway have been established as a requirement for glioblastoma (GBM) initiation and progression, which suggests that blockade of CDK4/6-Rb signaling axis for GBM treatment. Palbociclib, a selective inhibitor of the cyclin-dependent kinases CDK4/6, has been applied for breast cancer treatment. However, its efficacy against glioblastoma has not been well clarified. Here, effects of CDK4/6 inhibitors on various kinds of GBM cell lines are investiged and the functional mechanisms are identified. Data showed that cells with diverse PTEN status respond to palbociclib differently. Gain-of-function and loss-of-function studies indicated that PTEN enhanced the sensitivity of GBM cells to palbociclib in vitro and in vivo, which was associated with suppressions of Akt and ERK signaling and independent of Rb signaling inhibition. Hence, our findings support that palbociclib selectively suppresses GBM with wild-type PTEN, which provides preclinical evidence and a proof-of-concept that CDK4/6 inhibitor can be utilized as target drug for GBM treatment.